Th2 cells promote eosinophil-independent pathology in a murine model of allergic bronchopulmonary aspergillosis - Dietschmann, Axel; Schruefer, Sebastian; Krappmann, Sven; Vöhringer, David (European Journal of Immunology, 2020)
Repeated inhalation of airborne conidia derived from the fungus Aspergillus fumigatus (Af) can lead to a severe eosinophil-dominated inflammatory condition of the lung termed allergic bronchopulmonary aspergillosis (ABPA). ABPA affects about 5 million individuals worldwide and the mechanisms regulating lung pathology in ABPA are poorly understood. Here, we used a mouse model of ABPA to investigate the role of eosinophils and T cell-derived IL-4/IL-13 for induction of allergic lung inflammation. Selective deletion of IL-4/IL-13 in T cells blunted the Af-induced lung eosinophilia and further resulted in lower expression of STAT6-regulated chemokines and effector proteins such as Arginase 1, Relm-α, Relm-β, and Muc5a/c. Eosinophil-deficient ΔdblGata mice showed lower IL-4 expression in the lung and the number of Th2 cells in the lung parenchyma was reduced. However, expression of the goblet cell markers Clca1 and Muc5a/c, abundance of mucin-positive cells, as well as weight gain of lungs were comparable between Af-challenged ΔdblGata and WT mice. Based on these results, we conclude that T cell-derived IL-4/IL-13 is essential for Af-induced lung eosinophilia and inflammation while eosinophils may play a more subtle immunomodulatory role and should not simply be regarded as pro-inflammatory effector cells in ABPA.
CRIS-Team Scopus Importer:2020-03-20
Keywords: allergy; Aspergillus fumigatus; eosinophils; IL-4/IL-13; lung inflammation